2013
DOI: 10.1186/1471-2458-13-1116
|View full text |Cite
|
Sign up to set email alerts
|

The H1N1 pandemic: media frames, stigmatization and coping

Abstract: BackgroundThroughout history, people have soothed their fear of disease outbreaks by searching for someone to blame. Such was the case with the April 2009 H1N1 flu outbreak. Mexicans and other Latinos living in the US were quickly stigmatized by non-Latinos as carriers of the virus, partly because of news reports on the outbreak’s alleged origin in Mexican pig farms.MethodsIn this exploratory study we examined the psychological processes of cue convergence and associative priming, through which many people lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
164
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(177 citation statements)
references
References 56 publications
9
164
0
4
Order By: Relevance
“…Infectious disease outbreaks can spread rapidly, causing enormous losses to individual health, national economies, and social wellbeing. [1][2][3][4][5][6] Through the early detection of an infectious disease outbreak, a small outbreak can potentially be contained at the local level, thereby reducing adverse impacts. [7][8][9][10][11] Early detection has been and remains the current narrative of infectious disease surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Infectious disease outbreaks can spread rapidly, causing enormous losses to individual health, national economies, and social wellbeing. [1][2][3][4][5][6] Through the early detection of an infectious disease outbreak, a small outbreak can potentially be contained at the local level, thereby reducing adverse impacts. [7][8][9][10][11] Early detection has been and remains the current narrative of infectious disease surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout history, people have sought to allocate blame to someone in order to calm their fear of disease outbreaks (McCauley et al 2013). This fear and othering is often present with pandemics.…”
mentioning
confidence: 99%
“…This fear and othering is often present with pandemics. For example, the 2014 Ebola outbreak was considered an African problem resulting in discrimination against those of African descent (Monson 2013), while the 2009 H1N1 flu outbreak in the USA saw Mexican and migrant workers targeted for discrimination (McCauley et al 2013). In the past century, a number of serious outbreaks of influenza have developed in Southeast Asia, for example Avian H7N9 Influenza, 2013; H2N2 Pandemic, 1957‐1958; H1N1 Pandemic, 1918 (Sugalski & Ullo 2018).…”
mentioning
confidence: 99%
“…Winterbottom et al, 2008). This is noteworthy, because scientific advancements such as invasive medical treatments are often transferred to a broader public by media coverage (cf., McCauley et al, 2013) in which techniques for making the reported content more vivid and appealing (i.e., emotion-eliciting) are popular (cf. Gilbert and Ovadia, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, information about diseases and treatments is also consumed by unconcerned individuals. For instance, many newspapers have a regular page on health issues and medical research is frequently covered by different media (e.g., McCauley et al, 2013). What healthy and unconcerned lay people take from this communication might affect their future behavior (e.g., they may be concerned with the respective disease despite their health or they may want to give advice to somebody else).…”
Section: Introductionmentioning
confidence: 99%